DETERMINAN KUALITAS LAPORAN KEUANGAN PADA PEMERINTAH DAERAH KOTA PALEMBANG - Febi Karisma Putri, Febi Karisma Putri; Maria, Maria; Amri, Darul (Jurnal Riset Terapan Akuntansi, 2024)
The quality of the Palembang City government’s financial reports is the focus of this research, which seeks to answerquestions about the relationship between fixed asset asministration, internal control systems, and good governance. This research uses saturated samples as a sampling stategy. Using Statisticaal Product and service Solutions (SPSS) software version 26, this research uses a multiple linear regression analysis approach to examine primary data collected through questionnaires. The test results in this research found that the factors that influence the quality of financial reports consist of fixed asset administration, internal control systems, and good governance which contribute to better government financial reporting. The findings show that fixed asset administration, internal control systems, and good governance all contribute to higher quality government financial repost, with an impact size of 87,2%.Keywords: Quality of Government Financial Reports